Outcomes of autologous hematopoietic cell transplantation in myeloma patients aged ≥75 years. Issue 14 (6th December 2019) - Bashir, Qaiser; Chamoun, Kamal; Milton, Denái R.; Khan, Maliha; Ahmed, Sairah; Mehta, Rohtesh; Popat, Uday R.; Kebriaei, Partow; Nieto, Yago; Oran, Betul; Ciurea, Stefan O.; Hosing, Chitra; et al.
Abstract: There is limited data on the outcomes of autologous hematopoietic cell transplantation (auto-HCT) in myeloma patients, 75 or older. We retrospectively analyzed all myeloma patients ( n  = 72), aged ≥75, who underwent auto-HCT at our center between January 1, 2000, and December 31, 2015. All patients received melphalan ≥140 mg m −2 conditioning. At day-100, the cumulative incidence of non-relapse mortality was 1%. The overall response rate was 91% with 29% achieving complete/stringent complete remission. The median progression-free survival (PFS) was 31.4 months, and median overall survival (OS) was 72.8 months. The presence of high-risk cytogenetic abnormalities was associated with inferior PFS ( p  = 0.005) and OS ( p  = 0.005), while international staging system stage III was identified as a negative prognostic factor for OS ( p =  0.002 vs. stage II). We conclude that auto-HCT can be safely performed in myeloma patients 75 and older and is associated with encouraging response rates.